2013
DOI: 10.1590/s1516-31802013000100004
|View full text |Cite
|
Sign up to set email alerts
|

Potentially inappropriate medications among elderly Brazilian outpatients

Abstract: CONTEXT AND OBJECTIVES: In Brazil, few studies have investigated the prevalence of potentially inappropriate medications (PIMs) among elderly outpatients. This study aimed to determine the prevalence of PIMs prescribed for elderly outpatients, identify the PIMs most commonly involved, and investigate whether age, sex and number of medications are related to prescription of such medications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
4
10

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 45 publications
2
29
4
10
Order By: Relevance
“…Resultados semelhantes têm sido observados em investigações internacionais 30,31,32 e brasileiras 23,24,36 . Como já relatado em estudos anteriores, a polifarmácia tem sido associada a resultados negativos em saúde, como, por exemplo, reações adversas, interações medicamentosas, baixa adesão e síndromes geriátricas 9,37,38 . Corroborando esse quadro, a associação aqui observada evidencia um cenário de baixa qualidade da polifarmácia entre os idosos estudados, já que esta se constituiu em um fator de risco para o uso de medicamentos potencialmente inadequados.…”
Section: Métodosunclassified
“…Resultados semelhantes têm sido observados em investigações internacionais 30,31,32 e brasileiras 23,24,36 . Como já relatado em estudos anteriores, a polifarmácia tem sido associada a resultados negativos em saúde, como, por exemplo, reações adversas, interações medicamentosas, baixa adesão e síndromes geriátricas 9,37,38 . Corroborando esse quadro, a associação aqui observada evidencia um cenário de baixa qualidade da polifarmácia entre os idosos estudados, já que esta se constituiu em um fator de risco para o uso de medicamentos potencialmente inadequados.…”
Section: Métodosunclassified
“…Other studies have found a relationship of female and increased risk for PIMs (Faustino, Passarelli, Jacob-Filho, 2013;Baldoni et al, 2014;Cassoni et al, 2014).…”
Section: Discussionmentioning
confidence: 86%
“…Studies conducted in health primary care centers, outpatient clinics and long term care settings have also reported a strong association between polypharmacy and risk of PIMs in Brazil (Oliveira et al, 2012;Faustino, Passarelli, Jacob-Filho, 2013;Santos et al, 2013;Vieira de Lima et al, 2013;Cassoni et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prevalence rates vary considerably across different studies involving inpatients: 5.3 -40.7% in the USA, 16.3 -52.6% in Canada, 19.8% in Europe, and 38.5% in Portugal (Curtis et al, 2004;Fialová et al, 2005;Maio, Del Canale, Abouzaid, 2010;Nyborg, Straand, Brekke, 2012;Oliveira Martins et al, 2006). In Brazil, prevalence rates range between 15.6% and 41% (Faustino, Passarelli, Jacob-Filho, 2013;Passarelli, Jacob-Filho, Figueras, 2005). However, it is important to take into account which version of the Beers Criteria was used in each analysis.…”
Section: Discussionmentioning
confidence: 99%